Ameliorative effects of vanillin on potassium bromate induces bone and blood disorders in vivo - Ben Saad, H; Ben Amara, I; Krayem, N; Boudawara, T; Kallel, C; Zeghal, K M; Hakim, A (Cellular and Molecular Biology, 2015)
The objective of this study was to investigate the propensity of potassium bromate (KBrO3) to induce oxidative stress in blood and bone of adult mice and its possible attenuation by vanillin. Our results demonstrated, after KBrO3 treatment, a decrease of red blood cells and hemoglobin and a significant increase of white blood cell. A decrease in plasma levels of folic acid, vitamin B12 and iron was also noted. Interestingly, an increase of lipid peroxidation, hydroperoxides, hydrogen peroxide, advanced oxidation protein products and protein carbonyl levels in erythrocytes and bone was observed, while superoxide dismutase, catalase and glutathione peroxidase activities and glutathione, non-protein thiol and vitamin C levels were decreased. KBrO3 treatment resulted in blood and bone DNA fragmentation, a hallmark of genotoxicity-KBrO3-induced, with reduction of DNA levels. Calcium and phosphorus levels showed a decrease in the bone and an increase in the plasma after KBrO3 treatment. These biochemical alterations were accompanied by histological changes in the blood smear and bone tissue. Treatment with vanillin improved the histopathological, hematotoxic and genotoxic effects induced by KBrO3. The results showed, for the first time, that the vanillin possesses a potent protective effect against the oxidative stress and genotoxicity in bone and blood of KBrO3-treated mice.